Internal Model Current Decoupling Control Strategy for Induction Motors - Qiuyue Xie; Qiwei Xu; Tao Yang; Yuxiaoying Tu (Energies)
In order to improve the current dynamic performance of induction motor (IM) drive systems, an internal model current decoupling control strategy is proposed to suppress the stator’s internal coupling effect. First, the IM mathematical model in the complex frequency domain is established, and the expressions of the coupling terms are derived. Then, according to the zero-pole distribution diagram and Bode plots, the design details for the structure and parameters of the internal model controller are presented in a continuous domain, and the impact of stator inductance mismatch on decoupling performance is analyzed. In addition to considering sampling and control delays, the IM mathematical model is established in the discrete domain, and the principle of the controller parameter is presented. Finally, the experimental results prove that the proposed internal model current decoupling control strategy can effectively improve the dynamic performance of IMs. Compared with the traditional feedforward current decoupling control strategy, the proposed method has superior decoupling performance under the operating conditions of low switching frequency. At the same time, a better steady-state performance is obtained by the proposed internal model control strategy.